Эребуни. Памятник Урартского зодчества VIII-VI в. до н. э. - Ходжаш, С. И. (1979)
Chodzaš/Hodjaš, S. I. - Truchtanova, N. S. - Oganesjan/Hovhannesjan, K. L.; Erebuni. Ein Denkmal urartäischer Baukunst des 8.-6. Jahrh. v.Chr.